Intergovernmental Relations and the Challenges of Power Devolution: Federalism in Nepal - Acharya, Keshav Kumar; Zafarullah, Habib (Public Governance, Administration and Finances Law Review, 2025)
This study investigates the complexities and obstacles associated with intergovernmental relations (IGR) in Nepal’s emerging federal system. By conducting interviews with government officials and analysing key IGR mechanisms, the research identifies substantial obstacles to the effective cooperation, coordination and coexistence of federal, provincial and local governments. Some of the significant issues are a lack of genuine autonomy for subnational entities, fiscal imbalances, inactive dispute resolution bodies and an ambiguous division of responsibilities. The study uses a qualitative approach, analysing authority, resources and responsibilities in Nepal through 29 key informant interviews with government officials. It identifies themes related to coordination, power devolution and service delivery, and uses secondary sources to contextualise Nepal’s federal experiment within broader theoretical and comparative contexts. The study reveals that centralised control, political interference and ineffective institutions continue to hinder Nepal’s IGR framework, despite the constitutional provisions. The findings have significant implications for federal governance in Nepal, emphasising the necessity of overcoming structural obstacles, promoting genuine collaboration among government echelons, and empowering subnational entities. More broadly, the study contributes to the literature on federalism and IGR in developing democracies by illustrating the difficulties associated with translating constitutional principles into functional multi-level governance systems.